Plant antimicrobial peptides - Nawrot, Robert; Barylski, Jakub; Nowicki, Grzegorz; Broniarczyk, Justyna; Buchwald, Waldemar; Goździcka-Józefiak, Anna (Folia microbiologica, 2014)
Plant antimicrobial peptides (AMPs) are a component of barrier defense system of plants. They have been isolated from roots, seeds, flowers, stems, and leaves of a wide variety of species and have activities towards phytopathogens, as well as against bacteria pathogenic to humans. Thus, plant AMPs are considered as promising antibiotic compounds with important biotechnological applications. Plant AMPs are grouped into several families and share general features such as positive charge, the presence of disulfide bonds (which stabilize the structure), and the mechanism of action targeting outer membrane structures.
Keywords: kationické antimikrobiální peptidy; Antimicrobial Cationic Peptides; Plant Physiological Phenomena; Plants; penetrační peptidy; Biotechnology; biotechnologie; Anti-Infective Agents; rostliny; Cell-Penetrating Peptides; antiinfekční látky; Anti-Bacterial Agents; Antifungal Agents; antibakteriální látky; antifungální látky; fyziologie rostlin